Bioethics and Environmental Education as a Commitment to Sustainability (Revista Iberoamericana de Bioética, 2020)
This article analyses the importance of Bioethics and Environmental Education as essential tools for the conservation of the environment. Despite this, Environmental Education, as a discipline in general, has been undervalued in many areas. It is an established, fundamental vehicle for raising environmental awareness and consciousness in all sections of society. The article also looks at the problems arising from climate change denial, the lack of a unanimous consensus and the shortage of professionals specialized in transmitting scientific knowledge and environmental values.
Keywords: bioethics; environmental education; climate change; responsability; action